Exploring loss and damage from climate change and global perspectives that influence response mechanism in vulnerable communities - Cyril Joseph Effiong; Jamila Musa Wakawa Zanna; David Hannah; Fraser Sugden (Sustainable Environment)
Climate change has led to unprecedented environmental and socio-economic challenges globally, especially in vulnerable communities. Loss and damage refer to the residual effects of climate change, where adaptation and mitigation measures may not be enough to prevent adverse impacts. This study examines the impact of loss and damage caused by climate change in the Lower Niger River region of Nigeria and the influence of global perspectives on the region. The research adopted a mixed-methods approach, including a survey of 198 households and 13 interviews with key stakeholders. Furthermore, an open-source terra climate data of precipitation, runoff, and temperature covering a 30-year period (1990–2020) sourced from Climate Research Unit (CRU) dataset and analysed to show distribution of trends and patterns in climate variables. Similarly, we conducted a land use land cover change (1990–2020) to ascertain the level of changes. Findings from the study have revealed that the anthropogenic factors contribute to hydrological changes in the Lower Niger River Region and these changes result in climatic disasters like flooding which cause severe loss and damage of livelihood including loss of agricultural productivity, fisheries, and accessibility. While global efforts to mitigate and adapt to climate change are important, the study uncovers that the influence of global perspectives on the Lower Niger River Region is often limited by factors such as unequal power dynamics, insufficient funding, and a lack of local ownership of initiatives. The study suggests the need for sustainable land management, resolution of farmers/headers conflict and increased awareness as measures in addressing loss and damage.